Modeling the effects of cigarette smoke extract on influenza B virus infections in mice - Chavez, Jerald R.; Yao, Wangyuan; Dulin, Harrison; Castellanos, Jasmine; Xu, Duo; Hai, Rong (Frontiers in Immunology, 2023)
Influenza B virus (IBV) is a major respiratory viral pathogen. Due to a lack of pandemic potential for IBV, there is a lag in research on IBV pathology and immunological responses compared to IAV. Therefore, the impact of various lifestyle and environmental factors on IBV infections, such as cigarette smoking (CS), remains elusive. Despite the increased risk and severity of IAV infections with CS, limited information exists on the impact of CS on IBV infections due to the absence of suitable animal models. To this end, we developed an animal model system by pre-treating mice for two weeks with cigarette smoke extract (CSE), then infected them with IBV and monitored the resulting pathological, immunological, and virological effects. Our results reveal that the CSE treatment decreased IBV specific IgG levels yet did not change viral replication in the upper airway/the lung, and weight recovery post infection. However, higher concentrations of CSE did result in higher mortality post infection. Together, this suggests that CS induced inflammation coupled with IBV infection resulted in exacerbated disease outcome.